2021
DOI: 10.1029/2019wr026756
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hydraulic Geometry to High Gradient Rivers in Southern Ecuador

Abstract: The Ecuadorian river system is comprised of more than 2,000 rivers and streams formed primarily in the Andes Mountains and discharging into the Pacific and Atlantic Oceans. Steep channels with coarse bed material constitute the main components of mountainous drainage systems (Buckalew et al., 1998). These channels are the principal source of sediment to lower gradient channels downstream. Historically, lower gradient rivers have received more attention due, in part, to their proximity to large population cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…The lack of a relationship between discharge and channel bed slope, as shown by Equation , has also been reported by Carrillo et al. (2021), who studied high gradient rivers. For trueD $\tilde{D}$ and trueW $\tilde{W}$, all predictor variables are found to be significant.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The lack of a relationship between discharge and channel bed slope, as shown by Equation , has also been reported by Carrillo et al. (2021), who studied high gradient rivers. For trueD $\tilde{D}$ and trueW $\tilde{W}$, all predictor variables are found to be significant.…”
Section: Resultssupporting
confidence: 71%
“…𝐴𝐴 Q𝑄 , all predictor variables considered are found to be significant except for S v . The lack of a relationship between discharge and channel bed slope, as shown by Equation16, has also been reported byCarrillo et al (2021), who studied high gradient rivers. For 𝐴𝐴 P𝑃 is not a significant parameter for S c ,…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Numerous preceding studies have developed relationships among mean flow velocity, discharge, channel slope, water surface width and other stream parameters (e.g., Carrillo et al., 2021; Ferguson et al., 2019). For channel with rough bed, like pool‐riffle channels, some field works indicated that the exponent describing the mean velocity with discharge is between 0.48 and 0.6 (Comiti et al., 2007), of which our numerical work was also within the range.…”
Section: Discussionmentioning
confidence: 99%
“…Three products are provided: a bankfull river surface dataset, a bankfull river width dataset and a bankfull river surface area dataset. These datasets provide a fundamental basis for various studies on the QTP, the third pole of the world, including studies on geological geomorphology 13 , hydroinformatics 14 , biogeochemical cycles 15 , plateau ecology, etc.…”
Section: Background and Summarymentioning
confidence: 99%